2021
DOI: 10.1186/s12966-021-01178-9
|View full text |Cite
|
Sign up to set email alerts
|

Testing front-of-package warnings to discourage red meat consumption: a randomized experiment with US meat consumers

Abstract: Background Reducing red meat is a strategy to improve public health and mitigate climate change in the United States and other high-income countries. Policies requiring warnings on the front of red meat packages are a promising intervention to shift consumers towards healthier and more sustainable food choices. We aimed to explore participants’ reactions to health and environmental warning messages about red meat. Methods Between June and July 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…The primary objective of this research is to explore the efficacy of goal framing for discouraging red meat purchases by experimentally testing whether messages that convey the worsening of environmental harms or the reduction of environmental harms are perceived as more effective at discouraging beef purchases. Perceived message effectiveness is a predictor of longer-term behavior change [ 63 ] and is a widely-used measure in initial testing of messages because it tends to be sensitive to small differences between similar messages [ 64 , 65 , 66 , 67 , 68 ]. Given the paucity of research on goal framing for messages focused on discouraging red meat consumption, this was an exploratory study and as such, we did not have an a priori hypothesis about which type of message would elicit higher effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of this research is to explore the efficacy of goal framing for discouraging red meat purchases by experimentally testing whether messages that convey the worsening of environmental harms or the reduction of environmental harms are perceived as more effective at discouraging beef purchases. Perceived message effectiveness is a predictor of longer-term behavior change [ 63 ] and is a widely-used measure in initial testing of messages because it tends to be sensitive to small differences between similar messages [ 64 , 65 , 66 , 67 , 68 ]. Given the paucity of research on goal framing for messages focused on discouraging red meat consumption, this was an exploratory study and as such, we did not have an a priori hypothesis about which type of message would elicit higher effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Although perceived effectiveness is a marker for messages' potential to change behavior, more research is needed to assess whether red meat warnings influence red meat purchasing and consumption behaviors. To our knowledge, only one study has investigated the impact of health and environmental warnings on outcomes related to red meat purchases [27]. That study found that participants perceived health warnings and combined environmental and health warnings as more effective than environmental warnings.…”
Section: Plos Onementioning
confidence: 99%
“…Given that previous research has shown that perceived message effectiveness is predictive of behavioral change [35], it is unclear why even the health warnings did not reduce selection of red meat in that study. One possibility is that the behavioral task may not have been properly powered to detect differences [27], or that the simplistic nature of an online choice experiment does not reflect how warnings would influence purchasing decisions in the real world. Future research would be useful to understand whether such warnings would discourage meat purchases in a more realistic food retail environment.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations